Analisis Faktor Kesulitan Membaca Permulaan Pada Peserta Didik Kelas II - Suryani, Suryani; Yunika Afryaningsih; Risdiana, Risdiana (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This research aims to describe the factors of initial reading difficulties experienced by class II students at SDIS Raudhatul Ulum 2 Puguk. The background to this research is the large number of students in the lower classes who experience difficulties in beginning reading. The type of recearch used in this research is descriptive with a qualitive opproach carried out at SDIS Raudhatul Ulum 2 Puguk. The aim of this research is to find out how early reading defficulties occur in class II students and what factors influince students starting reading difficulties at SDIS Raudhatul Ulum 2 Pugu. Data collection techniques include interviews. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of research on factor Analysisof beginning reading difficulties in class II SDIS Raudhatul Ulum 2 Puguk can be said to be poor, including deletion of laters, reversal of words, repetition, lack of attention to punctuatoin, hesitation and stuttering.